MoTSEL: model of technology-supported learning for special educational needs learners in institutions for higher learning - Alias, Roslinda; Alias, Nor Aziah; Mokhtar, Azwadi (Universiti Teknologi MARA, Kedah, 2023)
Established formally in 2016, the Model of Technology-Supported Learning for Special Educational Needs Learners in Institutions for Higher Learning (MoTSEL) has significantly enriched inclusive education in Malaysia, particularly in institutions of higher learning (IHLs). MoTSEL was formulated through extensive needs assessments conducted among 66 SEN learners from eight public IHLs for its development. It was then evaluated and accepted by a panel of 11 subject matter experts (SMEs) through two rounds of the Delphi Technique. The model comprises of six vital components, namely: Academic Affairs, Student Affairs, Library, University Administration, Community, Industrial Networking and Alumni, and a Special Department/Unit for SEN learners. The exemplifications of the model have fueled numerous educational innovations, including E-ESSENCE, a social emotional support for SEN learners, and i-CHO Kit and My-CHO Kit, aimed at promoting understanding of disability needs among other learners via teaching kit. Remarkably, these innovations have been recognized and have won numerous awards, illustrating the tangible impact of the model. Serving as a reference for the Ministry of Higher Education's Guidelines for the Implementation of Inclusive Policy for Persons with Disabilities in Higher Education Institutions, the model led to the establishment of the UiTM Disability Services Unit. Its most notable accomplishment is its role as the foundational framework for the UiTM DSU, underlining its critical contribution in advancing inclusion, accessibility, and equal opportunities in Malaysian higher education